Analisis Penerapan Sistem Informasi Akuntansi Penggajian Pada Balai Konservasi Sumber Daya Alam Sumatera Selatan - Zein Ghozali; Irsan; Masnoni; Lia Sari; Rizki Vitalia (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to find out how the implementation of the Payroll Accounting information system at Nature Conservation Agency of South Sumatra is. The researcher uses qualitative descriptive research method because this research explores the phenomenon of State Civil Apparatus (ASN) and Government employees of Non Civil Servants (PPNPN) payroll process at Nature Conservation Agency of South Sumatra. The writer uses primary data in the form of interview and secondary material in the form of documents and regulations which collected from various sources. The conclusions of the research are: (1) South Sumatra BKSDA conducts ASN and PPNPN payroll stages starting from personnel and administrasion department. To change employee salary data and then it is sent to the Finance Department for further processed according to 8 types of salary, those are basic salary, supplementary salary, underpaid, continuous salary, thirteenth month salary, holiday allowance salary, meal allowances and other employee expenses in accordance with the applicable laws and regulations (2) In reporting the payroll, South Sumatra BKSDA does the manual recording process first, then inputted into the application so that it is recorded by the computer in accordance with the accounting standards of the prevailing Agency Accounting System. As for the suggestion, it is necessary to upgrade the competence of HR (Human Resources) in the salary system of the ASN and PPNPN, so that in absorbing the issuance of the latest government regulations regarding payroll the ASN and PPNPN can understand faster and implement it and also and also precise and ready in processing changes in employee data related to the salary amount of the ASN and PPNPN can be supported by a sufficient number of implementing employees so that the workload can be divided according to their duties and functions